The Study of Relationship and Validation of Action Competence for Environment Model of Grade 12 Students - khunwandee, Suriya; Ketsing, Jeerawan (Journal of Inclusive and Innovative Education, 2023)
Action competence (AC) for environment is an important learning outcome in environmental education that aims to prepare citizens to deal with environmental problems and create sustainability for the environment, society, and economy. Previous studies reveal that many researchers have proposed AC components. However, there is no research focused on the validation of the correlation among these components, and the AC model. Therefore, this research is intense to address this research gap. The samples were 191 grade 12 students obtained from the Stratified random sampling technique. The data were collected from a questionnaire in a 3-level Likert-scale format. It consisted of six AC components. The reliability coefficient was 0.87. Student responses were analyzed by Pearson's correlation coefficient and confirmatory factor analysis. The results show that AC components have a positive relationship, and a model of the AC is well fitted with the empirical data (p-value = 0.074, X2/df=1.743, CFI=0.987, TLI=0.978, RMSEA=0.062). In addition, the thinking skills for action are the AC component that had the highest weight, 0.81. This research suggests that to develop AC, learners should be provided with opportunities to practice thinking skills, in this case critical thinking and reflective thinking, while solving environmental problems.